Bidding for nothing?: the pitfalls of overly neutral framing - Dürsch, Peter; Müller, Julia (Applied economics letters, 2017)
Neutral framing is a standard tool of experimental economics. However, overly neutral instructions, which lack any contextual clues, can lead to strange behaviour. In a contextless second-price auction for a meaningless good, a majority of subjects enter positive bids - likely a case of cognitive experimenter demand effect. Subjects may interpret the lack of context as being tasked with bidding in the experiment. Adding another auction that has a context drastically reduces the positive bids in the meaningless auction.
Gesehen am 26.09.2018
Published online: 12 Oct 2016